Thousands of models, one story: current account imbalances in the global economy - Alexander Chudik; Alistair Dieppe; Michele Ca' Zorzi (European Central Bank (ECB), 2012)
The global financial crisis has led to a revival of the empirical literature on current account imbalances. This paper contributes to that literature by investigating the importance of evaluating model and parameter uncertainty prior to reaching any firm conclusion. We explore three alternative econometric strategies: examining all models, selecting a few, and combining them all. Out of thousands (or indeed millions) of models a story emerges. Prior to the financial crisis, current account positions of major economies such as the US, UK, Japan and China were not aligned with fundamentals.
Keywords: C11; C33; F32; F34; F41; O52; 330; current account; global imbalances; model combination; Model uncertainty; panel data